2019
DOI: 10.4014/jmb.1903.03033
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Identification of Bacillus cereus Group Species Using Low Mass Biomarkers by MALDI-TOF MS

Abstract: Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS)-based pathogen identification relies on the ribosomal protein spectra provided in the proprietary database. Although these mass spectra can discern various pathogens at species level, the spectra-based method still has limitations in identifying closely-related microbial species. In this study, to overcome the limits of the current MALDI-TOF MS identification method using ribosomal protein spectra, we applied MALDI-TOF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 43 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…However, peak-specific analysis allowed the distinction of the three serovars. This approach, based on the identification of specific protein peaks produced by MALDI–TOF MS, has been used in previous studies to improve the identification rate of different subtypes of the same species, such as Listeria monocytogenes , Vibrio parahaemolyticus , Bacillus cereus , and Streptococcus species [ 20 , 25 , 26 , 27 , 28 ]. However, MALDI–TOF–MS-based subtyping for applications such as the identification of serovars, antibiotic resistance strains, and clonal complexes is still challenging and requires careful data analysis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, peak-specific analysis allowed the distinction of the three serovars. This approach, based on the identification of specific protein peaks produced by MALDI–TOF MS, has been used in previous studies to improve the identification rate of different subtypes of the same species, such as Listeria monocytogenes , Vibrio parahaemolyticus , Bacillus cereus , and Streptococcus species [ 20 , 25 , 26 , 27 , 28 ]. However, MALDI–TOF–MS-based subtyping for applications such as the identification of serovars, antibiotic resistance strains, and clonal complexes is still challenging and requires careful data analysis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted already on the applicability of MALDI-TOF MS in the identification/discrimination of related species, as for members of the B. cereus group [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, genes such as 16S rRNA, 16S-23S rRNA intergenic spacer region, and the elongation factor Tu (tuf) gene have been used to distinguish microorganisms at the species or subspecies level [4,9,[26][27][28][29]. However, some studies have reported that these genes share high sequence similarities without showing sufficient variabilities to allow for the differentiation between L. delbrueckii subspecies [4,13].…”
Section: Genetic Marker Specificity Testmentioning
confidence: 99%